Implementation of location awareness and sharing system based on GPS and GPRS using J2ME, PHP and MYSQL - Chandra, A; Jain, S; Qadeer, M A (2011 3rd International Conference on Computer Research and Development, 2011)
This document provides detail on the implementation of a location awareness system which gives the user's current location, sends this location using SMS (Short Message Service) plus sharing location with friends and family and view them on Google maps. Users can also take benefit of this application in emergency situations by using emergency feature of this application. To get the location coordinates, application is using GPS (Global Positioning System) as location provider. The application design has five parts: a mobile client, a web server, a database, GPS system and a map service. A mobile client which consists of a mobile and GPS receiver finds the location of the user to get aware of his location. In order to share this location the mobile client sends this location to the web server from where other users can get this location if they have the authentication provided by the user. The mobile client is implemented using J2ME which is one of the most promising software platforms for mobile devices. Sun representatives assert that 18 to 20 million mobile phones support the J2ME platform. Analysts predict that within the next few years, this technology will become omnipresent. According to Gartner Group estimates, in 2006, approximately 80 percent of mobile phones will support Java. The web server side programming is done using PHP and database is maintained by MYSQL.